Iron Metabolism of the Skeletal Muscle and Neurodegeneration - Halon-Golabek, Malgorzata; Borkowska, Andzelika; Herman-Antosiewicz, Anna; Antosiewicz, Jedrzej (Frontiers in Neuroscience, 2019)
Recent studies clearly indicate that the endocrine function of the skeletal muscle is essential for a long and healthy life. Regular exercise, which has been shown to stimulate the release of myokines, lowers the risk of many diseases, including Alzheimer’s and Parkinson’s disease, emphasizing the role of skeletal muscle in proper functioning of other tissues. In addition, exercise increases insulin sensitivity, which may also impact iron metabolism. Even though the role of iron in neurodegeneration is well established, the exact mechanisms of iron toxicity are not known. Interestingly, exercise has been shown to modulate iron metabolism, mainly by reducing body iron stores. Insulin signaling and iron metabolism are interconnected, as high tissue iron stores are associated with insulin resistance, and conversely, impaired insulin signaling may lead to iron accumulation in an affected tissue. Excess iron accumulation in tissue triggers iron-dependent oxidative stress. Further, iron overload in the skeletal muscle not only negatively affects muscle contractility but also might impact its endocrine function, thus possibly affecting the clinical outcome of diseases, including neurodegenerative diseases. In this review, we discuss possible mechanisms of iron dependent oxidative stress in skeletal muscle, its impact on muscle mass and endocrine function, as well as on neurodegeneration processes.